Comparativa de eficacia entre miel de abeja y sulfadiazina de plata en la cicatrización de quemaduras en pacientes pediátricos: una revisión de la literatura - Rodríguez Freire, Vanessa Katherine (2025)
Pediatric burns are the fourth cause of mortality in infants and this population is taken into account due to the factors that trigger burns and their tissue involvement. It should be noted that, by using healing methods with silver sulfadiazine mostly, but has made the use of honey for the healing of these injuries making a comparison both in benefits, healing time and its reaction to opportunistic pathogens and that in ancient times and should be taken into account today. The objective of this research is based on comparing bee honey with sulfadiazine in the healing of pediatric burns from a literature review, being the line of research Nursing Management in health services, the methodology used was a qualitative research, using the Prisma method that included original articles, reviews, case studies, editorials and technical publications directly related to bee honey, its benefits its application in burns in the pediatric population in the year 2019-2024, different languages coming from databases such as: Mendeley, Scielo, PubMed. The information search and selection process yielded a total of 10 articles with which the review was developed with the development of the research. It is concluded that bee honey with its antimicrobial and antioxidant benefits gives way to an accelerated recovery of pediatric patients suffering burns with silver sulfadiazine.